Calcination/phosphorization of dual Ni/Co-MOF into NiCoP/C nanohybrid with enhanced electrochemical property for high energy density asymmetric supercapacitor. (10th October 2019) - Zhou, Qingfeng; Gong, Yun; Tao, Keyu
Abstract: Binary metal compounds have higher conductivity and richer redox reactions due to the co-existence and synergism of different transition metals. Besides, carbon in composite materials has the advantage of enhancing electronic conductivity to promote fast electron transmission. Herein, a series of Nim Pn /C, Ni2 P/C, Co2 P/C and Nix Co2-x P/C nanohybrids with different Ni/Co molar ratios were synthesized by in-situ calcination/phosphorization of MOF precursors. These nanohybrid materials were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, energy dispersive spectrometer and electrochemical tests. The NiCoP/C material possesses a granular structure with NiCoP nanoparticles anchored in a large number of carbon. Taking advantage of the bimetallic synergism and carbon anchoring effect, the as-prepared NiCoP/C sample delivers the most prominent specific capacities of 775.7C g −1 at 1 A g −1, and 582.4C g −1 at 20 A g −1 (20-fold) with a superior rate capability of 75.1% retention, much superior to those of the corresponding Nim Pn /C, Ni2 P/C, Co2 P/C, other Nix Co2-x P/C samples and various reported metal phosphide nanostructures/nanocomposites. Furthermore, the constructed NiCoP/C//activated carbon asymmetric supercapacitor can exhibit a high energy density of 47.6 Wh kg −1  at a power density of 798.9 W kg −1, which was superior to those previously reported of Ni/Co phosphide nanomaterials. Graphical abstract: Image 1 Highlights: Nim Pn /C and Nix Co2-x P/C nanohybrids have been synthetised by in-situ calcination/phosphorization of the corresponding MOF. Synergistic effect of Ni and Co significantly enhanced the electrochemical performance of Ni2 P and Co2 P. NiCoP/C possesses high specific capacity and superior rate performance. High energy density of 47.6 W h kg −1 at 798.9 W kg −1 can be obtained in ASC device.